Knowledge of farmers about animal management and prevalence of reproductive disorders in cows at Babugonj Upazila under Barisal district of Bangladesh (Journal of the Bangladesh Agricultural University, 2017)
The purposes of the study were to evaluate the existing cattle management system, outbreak of reproductive disorders and farmer’s knowledge about cattle rearing. The data were collected from a sample of 100 farm household heads selected out of a total of 1000 farm household heads from Babugonj upazila through multi-stage random sampling technique interview with a pretested questionnaire during the period from January to April 2015. In this survey, we found that 65% farmers were using semi intensive housing system of cattle and 90% did not de-worm their cattle regularly. Only 3% farmers attended a training course related to animal rearing. None of the farmers maintained a register and calculated the feeding cost per month. About 97% farmers faced the problem of reproductive disorders. Still 77% farmers wereusing natural insemination for their cow’s breeding. A total of 200 cows’ history of reproductive disorder was collected. The prevalence of anoestrus,  repeat breeding,  metritis,  poor heat detection,  ovarian cyst,  uterine prolapse,  vaginal prolapse, retained placenta, abortion, still birth,  dystocia,  pyometra and laceration of vagina were 22.0% (44), 14.0% (28), 9.5% (19), 24.0% (48), 1.5% (3), 1.0% (2), 0.5% (1), 9.0% 18), 2.0% (4), 2.5% (5), 3.0% (6), 3.0% (6) and 8.0% (16), respectively. It may be concluded that the knowledge of farmer about cattle management is very poor which influenced the high prevalence of reproductive disorders. The farmers need training on hygienic management and reproduction of cows.J. Bangladesh Agril. Univ. 15(2): 272-275, December 2017